2006
DOI: 10.1111/j.1365-2109.2005.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of physical behaviour of feed pellets in Mediterranean water

Abstract: Settled uneaten feed causes the most intense impact under sea cages, and settling velocity of the feed pellets represents a key parameter for waste dispersion models. Even if some data about physical properties of feed pellets have been published in the framework of salmonid rearing, there is a complete lack of information related to the Mediterranean Sea, as regards typical values of temperature, salinity and feed composition for Gilthead Sea Bream (Sparus aurata L.) and Sea Bass (Dicentrarchus labrax L.). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 14 publications
1
24
2
2
Order By: Relevance
“…Differences in fish abundance and species composition recorded at the SB and ABT farms may be related to the type of food used and/or the type of habitat at each farm. Whole baitfish differ substantially in their nutrient composition, food size and settling velocity from the food pellets used at SB farms (Vassallo et al 2006). Šegvić Bubić et al (2011) suggested that the pellets and their fine particulates may attract a more diverse fish community and can be more easily consumed than baitfish.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in fish abundance and species composition recorded at the SB and ABT farms may be related to the type of food used and/or the type of habitat at each farm. Whole baitfish differ substantially in their nutrient composition, food size and settling velocity from the food pellets used at SB farms (Vassallo et al 2006). Šegvić Bubić et al (2011) suggested that the pellets and their fine particulates may attract a more diverse fish community and can be more easily consumed than baitfish.…”
Section: Discussionmentioning
confidence: 99%
“…Cage aquaculture can release a considerable amount of biogenic waste such as organic wastes and inorganic nutrients that are generated in the production process (Troell & Norberg 1998, Cheshuk et al 2003, Vassallo et al 2006, Redmond et al 2010. The rapid expansion of cage aquaculture has raised a general concern about increasing amounts of solid and dissolved nutrients released to the aquatic environment (Perez 2002, Whitmarsh et al 2006, Redmond et al 2010, Azevedo et al 2011, Skriptsova & Miroshnikova 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Estos coeficientes fueron corregidos bajo el supuesto de que aproximadamente un 5% del alimento introducido a las jaulas no es consumido por los peces. Este porcentaje es considerado como un valor típico para el alimento no consumido (Vassallo et al 2006), aunque en la actualidad este porcentaje puede variar de valores más pequeños para piscifactorías de salmón Atlántico altamente tecnificadas hasta 20% para piscifactorías más pequeñas y con menos tecnología.…”
Section: Caracterización De Los Residuos De La Piscifactoríaunclassified
“…Las partículas de alimento no consumido caen aproximadamente 3 veces más rápido que las partículas fecales (Gowen et al 1989), pues las velocidades de sedimentación son entre 6 y 14 cm s -1 para partículas de alimento (Panchang et al 1997, Doglioli et al 2004, Vassallo et al 2006, Piedecausa et al 2009), y entre 0.05 y 7.5 cm s -1 para partículas fecales (Panchang et al 1997, Doglioli et al 2004, Piedecausa et al 2009). Con base en estos estudios, las velocidades de sedimentación consideradas en este documento…”
Section: Caracterización De Los Residuos De La Piscifactoríaunclassified
See 1 more Smart Citation